Effective atomic orbitals: A tool for understanding electronic structure of molecules. Issue 16 (6th February 2014) - Mayer, István; Brändas, Erkki; Szabados, Ágnes; Surján, Péter
<x xml:space="preserve">Abstract</x> It is discussed that one can obtain effective atomic orbitals (AOs) in quite different theoretical frameworks of Hilbert‐space and three‐dimensional (3D) analyses. In all cases, one can clearly distinguish between the orbitals of an effective minimal basis set and orbitals which are only insignificantly occupied. This observation makes a solid theoretical basis beyond our qualitative picture of molecular electronic structure, described in terms of minimal basis AOs having decisive participation in bonding, and may be considered as a quantum chemical manifestation of the octet rule. For strongly positive atoms like the hypervalent sulfur, some weakly occupied orbitals reflecting "back donation" can also be identified. From the conceptual point of view, it is very important that AOs of characteristic shape can be obtained even by processing the results of plane wave calculations in which no atom‐centered basis orbitals were applied. The different types of analyses (Hilbert‐space and 3D) can be done on equal footing, performing quite analogous procedures, and they exhibit an unexpected interrelation, too. © 2014 Wiley Periodicals, Inc.